MODEL PENCEGAHAN TUBERKULOSIS PARU DI KABUPATEN MAROS PROVINSI SULAWESI SELATAN - Yermi Yermi; Aminah Aminah (Pascasarjana Universitas Negeri Makassar, 2022)
The study aims to describe the relationship of knowledge, attitude, and performance in the disease prevention models with pulmonary tuberculosis incidence in Maros South Sulawesi. The study is designed in cross sectional model with a population of 312 people and 102 are selected as respondents. A statistical bivariate with chi square test and multivariate with logistic regression are employed. This study indicates that knowledge in the primary prevention model is p = 0,015, in the secondary prevention model is p = 0,038, performance in the primary prevention model is p = 0,029, in the secondary prevention model is p = 0,027, and in the tertiary prevention model is p = 0,034 in their relationship with pulmonary tuberculosis incidence. Knowledge in the tertiary prevention model is p = 1,000, attitudes in the primary prevention model is p = 0,111, in the secondary prevention model is p = 0,119, and attitudes in the tertiary prevention model is p = 0,198 have no relationship with the pulmonary tuberculosis incidence. The multivariate logistic regression test proves that performance second prevention model is the most influential factor on the pulmonary tuberculosis incidence (wald = 2,345, p = 0,126).